Maximizing RNA yield from archival renal tumors and optimizing gene expression analysis - Glenn, Sean T; Head, Karen L; Teh, Bin T; Gross, Kenneth W; Kim, Hyung L (Journal of biomolecular screening, 2010)
Formalin-fixed, paraffin-embedded tissues are widely available for gene expression analysis using TaqMan PCR. Five methods, including 4 commercial kits, for recovering RNA from paraffin-embedded renal tumor tissue were compared. The MasterPure kit from Epicentre produced the highest RNA yield. However, the difference in RNA yield between the kit from Epicenter and Invitrogen's TRIzol method was not significant. Using the top 3 RNA isolation methods, the manufacturers' protocols were modified to include an overnight Proteinase K digestion. Overnight protein digestion resulted in a significant increase in RNA yield. To optimize the reverse transcription reaction, conventional reverse transcription with random oligonucleotide primers was compared to reverse transcription using primers specific for genes of interest. Reverse transcription using gene-specific primers significantly increased the quantity of cDNA detectable by TaqMan PCR. Therefore, expression profiling of formalin-fixed, paraffin-embedded tissue using TaqMan qPCR can be optimized by using the MasterPure RNA isolation kit modified to include an overnight Proteinase K digestion and gene-specific primers during the reverse transcription.